Partition polynomials assigned by parafunctions of triangular matrices with arbitrary first two columns - Stefluk, S.D. (Carpathian Mathematical Publications, 2014)
We research a wide class of partition polynomials that satisfy paradeterminants of slopping triangular matrix with two arbitrary first columns.